Comparison of intellectual and professional service contract evaluation procedure : PPR-2008 Vs World Bank and ADB - Islam, Md. Rashedul (BRAC University, 2013)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.